Peer Bullying Levels of Students Studying in Advantageous and Disadvantaged Schools - Sena Koca; Furkan Direk; Ayşe Türksoy Işım; Hasan Ceyhun Can; Zarife Taştan (IUC University Press, 2024)
Within the scope of this research, it was aimed to examine the peer bullying levels of secondary school students in regional schools, which can be classified as advantageous and disadvantaged. For this purpose, students' peer bullying tendencies were assessed to examine whether there are differences according to the variables of participation in sports, gender, number of siblings, general emotional state at home and parents' education level. The research was designed in a relational research design. The sample of the research consisted of a total of 594 students, 313 (52.7%) of whom were female and 281 (47.3%) of whom were male, selected by criterion sampling, one of the purposeful sampling methods, from high schools located in advantageous and disadvantaged regions. In the study, in addition to the personal information form, the "Student Relations Attitude Scale" was applied to the participants in order to determine the students' peer bullying levels. Independent sample t-test and One-way ANOVA were applied to analyze the data. It has been observed that the tendency toward bully personality is higher among students studying in disadvantaged regional schools, students with more than one sibling, and students who are angry/tensed at home. It was determined that the level of self-confidence was high in male students and students who were peaceful at home. It has been determined that avoidance from bullying is higher in students studying in advantaged regions, students with at least one sibling, students who do licensed sports, and students who are peaceful at home. When peer bullying levels were examined according to the education level of the parents, it was found that students whose parents were undergraduate or graduate students showed more avoidance from bullying behavior than students whose parents were primary school graduates. It has been observed that students with parents who are primary school graduates tend to show more bully personality than students whose parents are secondary school graduates. In conclusion, it is seen that playing sports promotes positive peer relationships and the region where the school is located influences the occurrence of peer bullying. Therefore, implementing intervention programs to prevent peer bullying experienced by students in schools is important for the development of positive feelings toward school.